2006
DOI: 10.1007/s00420-005-0073-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peripheral blood neutrophil leucocytes in lead-exposed workers

Abstract: Our study is the first to describe a dose-dependent effect of lead on ANC in exposed workers. Our results underline the importance of promoting a further reduction of occupational lead exposure levels, adopting adequate individual protection means, as well as conducting medical campaigns against smoking, at the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Serum levels ofTNF-a and G-CSF were found to be clearly higher in workers exposed to low-moderate doses of lead as compared with NE workers. ANC was confirmed to be significantly higher in E workers than NE workers, as reported in a previous study (10). When smoking status was considered, current smokers had higher levels of TNF-a and G-CSF than non-smokers among E workers and, to a smaller extent, among NE workers.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Serum levels ofTNF-a and G-CSF were found to be clearly higher in workers exposed to low-moderate doses of lead as compared with NE workers. ANC was confirmed to be significantly higher in E workers than NE workers, as reported in a previous study (10). When smoking status was considered, current smokers had higher levels of TNF-a and G-CSF than non-smokers among E workers and, to a smaller extent, among NE workers.…”
Section: Discussionsupporting
confidence: 83%
“…chemotaxis (8)(9) and nitroblue tetrazolium reduction in lead-exposed workers (8). Moreover, we previously reported a significantly higher blood absolute neutrophil count in lead-exposed workers with respect to non-exposed controls (10). This effect resulted to be dose-dependent and a significant interaction of lead exposure with smoking habit was also demonstrated.…”
mentioning
confidence: 76%
“…Long-term lead exposure can cause encephalopathy, peripheral neuropathy, cognitive delays, anemia, and digestive and renal issues [ 1 , 2 ]. Chronic occupational lead poisoning is an issue in China, and unfortunately is also common in European countries and the U.S. [ 3 , 4 ]. Long-term lead exposure below occupational exposure limits (OELs) may cause a variety of sub-clinical problems, as well as chronic lead poisoning [ 5 , 6 , 7 ], suggesting that existing OELs may need amendment.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these observations, Quieroz et al [46] suggested that immune dysfunction may be a sensitive indicator of exposure to Pb. More recently, Di Lorenzo et al (2006) reported an association between Pb exposure and the numbers of circulating neutrophils, with the strongest association being observed in occupationally-exposed workers who smoked [49]. This latter observation is not surprising given the well-recognized association of smoking with: i) neutrophilia [50]; and ii) increased levels of Pb in the blood of smokers as described above.…”
Section: Leadmentioning
confidence: 78%
“…Although the authors speculate that increased numbers of circulating neutrophils may represent a mechanism to compensate for Pb-mediated immune dysfunction, they concede that it is more likely to reflect a neuroendocrine response to toxicity/stress. In this setting, increased production of endogenous glucocorticoids and catecholamines may contribute to both neutrophilia and neutrophil dysfunction possibly by interfering with the adhesion of these cells to vascular endothelium [49].…”
Section: Leadmentioning
confidence: 99%